Investigating the Effect of Women’s Personality Type on the purchase intention (Approach: Women Archetypes) - Nazari, Faezeh Hedayat; Teimouri, Nazanin; Narenjbon, Ahmad Darvish (International Journal of Psychosocial Rehabilitation, 2020)
Today, one of the most important and decisive issues in the success of companies’ marketing activities is to know more consumers so that they can maintain the attractiveness of their product to the market. The issue of how to create different preferences in the consumer is related to different motivations and their personalities. Jung recognized the generality and repetition of the characters and events of human life and called these universal events “myths” and “archetypes” The archetype or goddesses are the powerful and invisible forces that shape the behavior and emotions of women. Recognition of these inner forces opens a new frontier for raising women’s awareness. By knowing which goddess is the dominant force of the inner personality, one can achieve one’s special instincts, priorities and abilities, as well as insight into women’s lives. Therefore, the use of archetypes can be a good platform for effectively shaping consumers’ image of products, as well as understanding the decision- making behavior and purchase intention them. Accordingly, the present study was conducted with the aim of better understanding consumers and studying personality traits through different types of eternal faces in women to be able to analyze the different tendencies of different groups and make suggestions in the area of influencing consumer-purchasing behavior. In this study, feminine archetypes include: “Artemis”, “Athena”, “Hastia”, “Hera”, “Demeter”, “Persephone” and “Aphrodite”, which are considered as dimensions of the personality type and based on those hypotheses were identified and the effect of different personality types on the individual’s attitude toward product involvement, product knowledge and brand image on the desire to buy products -women’s clothing of “Holiday” production group was investigated. The sample studied in this study were 389 consumers of “Holiday” products in Tehran who were selected by cluster sampling from ten main “Holiday” stores. The personality type of the respondents was measured using the “Shinoda Bolen” questionnaire and also their attitudes toward the studied variables were measured using a questionnaire based on a five-option Likert scale. Cronbach’s alpha coefficient of the questionnaire was calculated to be 0.773, which has a high validity. The collected data were analyzed using SPSS software and statistical tests including: one-factor variance, ANOVA, Fisher, and regression were used. Findings from the test of research hypotheses showed that consumers with different personality types have significant differences in terms of product involvement, product knowledge, and purchase intention the product. Based on these differences, the company was advised to carry out its marketing plans in a way that was tailored to their individual eternal form to attract the attention of different personality types.